The importance of wrist flexion and x-factor in the golf swing: a forward kinematic approach - Sweeney, M.; Mills, P.; Alderson, J.; Elliott, B. (ISBS - Conference Proceedings Archive (Konstanz), 2011)
This study aimed to investigate the importance of wrist flexion and trunk rotation relative to the pelvis about a vertical axis (X-factor) in the golf swing, through the use of kinematic simulation. Empirical data of 5 highly skilled golfers were collected using a 3D optoreflective system. A full body, 3D forward kinematic model was created that predicted the endpoint of the club to within 0.02 mm of the empirical data. X-factor rotation, then flexion of the wrist was locked at zero degrees throughout the downswing, with the effect on the kinematics of the club-head analysed. The results indicated that effective extension/flexion at the wrist is of great importance to performance with an average reduction of club-head velocity at impact of 46%, when wrist flexion is restricted during the downswing. Effective rotation of the trunk was also important to performance variables.